1993
DOI: 10.1126/science.8248780
|View full text |Cite
|
Sign up to set email alerts
|

A Third Recognition Element in Bacterial Promoters: DNA Binding by the α Subunit of RNA Polymerase

Abstract: A DNA sequence rich in (A+T), located upstream of the -10, -35 region of the Escherichia coli ribosomal RNA promoter rrnB P1 and called the UP element, stimulates transcription by a factor of 30 in vivo, as well as in vitro in the absence of protein factors other than RNA polymerase (RNAP). When fused to other promoters, such as lacUV5, the UP element also stimulates transcription, indicating that it is a separate promoter module. Mutations in the carboxyl-terminal region of the alpha subunit of RNAP prevent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
746
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 713 publications
(788 citation statements)
references
References 58 publications
40
746
0
2
Order By: Relevance
“…The present results indicate that this UP element plays an important role in maintaining the high promoter activity of cspA at both 37ЊC and low temperature. Such an AT-rich sequence, called the UP element, located upstream of the ¹35 region has been shown to play an important role in enhancing transcription (Ross et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The present results indicate that this UP element plays an important role in maintaining the high promoter activity of cspA at both 37ЊC and low temperature. Such an AT-rich sequence, called the UP element, located upstream of the ¹35 region has been shown to play an important role in enhancing transcription (Ross et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA promoter region shows characteristics of a promoter UP element, which are constituted by AT-rich regions of 20 bp spanning from ¹40 to ¹60 with a possible non-perfect inverted repeat. It has been demonstrated that these UP elements are the target sites of the C-terminal domain ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 26, 361-372 of the ␣-subunit of RNA polymerase, thereby enhancing transcription (Ross et al, 1993;Attey et al, 1994;Landini and Volkert, 1995). In the case of the rrnB P 1 promoter of E. coli, interaction of ␣ with the UP element enhances promoter activity by approximately 30-fold (Ross et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that these UP elements are the target sites of the C-terminal domain ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 26, 361-372 of the ␣-subunit of RNA polymerase, thereby enhancing transcription (Ross et al, 1993;Attey et al, 1994;Landini and Volkert, 1995). In the case of the rrnB P 1 promoter of E. coli, interaction of ␣ with the UP element enhances promoter activity by approximately 30-fold (Ross et al, 1993). We have shown that the C-terminal region of the ␣-subunit binds the cagA P 1 UP-like element protecting DNA positions ¹14 to ¹70 from DNase I digestion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, this mutant RNA polymerase or variants possessing certain substitutions in the C-terminal region failed to activate certain transcription factor-dependent promoters subsequently defined as class I activator-dependent promoters (such as lacP1, P uxuAB , P ompC ) and some UP-element-stimulated promoters (such as rrnB P1, P RNA-II , P leuV ) while retaining transcriptional proficiency at promoters independent of class I transcription factors and AT-rich UP-elements (such as galP1 and the pstS promoter) Igarashi et al 1991a;Zou et al 1992;Ross et al 1993;Murakami et al 1996).…”
Section: ᭧ Blackwell Science Limitedmentioning
confidence: 99%